Parosteal lipoma of humerus—A rare case() - Chaudhary, Rohan Jagat (Elsevier, 2013)
INTRODUCTION: Parosteal lipoma is an extremely rare benign tumor composed mainly of mature adipose tissue with a bony component. PRESENTATION OF CASE: This study reports the case of a 65-year old woman with a big mass on the posteromedial aspect of the right upper arm since 1 year. The swelling was a slow growing, painless, nontender, immobile mass which was not fixed to skin. She had no complaints of painful or restricted movements of the shoulder joint. She had no history of trauma to the upper limb. MRI revealed a large 13 cm × 5 cm × 8 cm well defined, nonenhancing, lobulated, heterointense, predominantly fat intensity lesion with a small area of chondroid component measuring 2 cm × 1.6 cm in posteromedial aspect of proximal right humerus, seen completely separate from the adjacent muscles. DISCUSSION: The patient underwent surgery under general anesthesia. Vertical elliptical incision was taken over the posterior border of the upper arm over the mass. The tumor was below the lower part of deltoid near the upper end of humerus, which formed the roof, and between the long and medial heads of triceps muscles. A part of tumor, measuring 6 cm × 5 cm × 5 cm, was under the long head of triceps displacing it along with radial nerve and vessels medially while the other part, measuring 7 cm × 6 cm × 3 cm, was under the medial head of triceps displacing it laterally. The tumor was excised undocking its periosteal attachment. The specimen weighed 250 g. On histopathology, the lesion was composed of mature lipocytes that had an intimate relationship with the periosteum. No cellular atypia or lipoblasts were seen. CONCLUSION: Parosteal lipomas are rare neoplasias with no proven malignant potential. These tumors can be resected without much damage to the adjacent structures, thus preserving the function of the upper limb.